Antioxidant Activity, Total Phenolic and Flavonoid Content, and Metabolite Profiling of Kalanchoe Ceratophylla Haw. Leaf Ethanol Extract - Luthfiyanti, Rohmah; Elya, Berna; Hanafi, Muhammad; Manalu, Lamhot Parulian; Maryana, Erma; Rahman, Taufik (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Kalanchoe ceratophylla Haw. is a species from the Crassulaceae genus known for its various pharmacological benefits, including antioxidant and antidiabetic effects, due to the high contents of flavonoids, tannins, and other phenolic compounds. This study aims to determine the antioxidant activity, total phenolic and flavonoid content, and metabolite profiling of ethanol extracts from K. ceratophylla Haw. leaves. The study utilized K. ceratophylla Haw. leaves, which were pre-identified and authenticated. Extraction was performed using maceration with 70% and 95% ethanol as solvents. The leaves were dried at 40 °C and freeze-dried at -20 °C to -30 °C. The metabolite profiles of the extracts were analyzed using high-resolution mass spectrometry (LC-HRMS) and gas chromatography-mass spectrometry (GC-MS). The HR-MS and GC-MS analyses confirmed the presence of antioxidants, flavonoids, and phenolics in the extract. The findings indicate that the drying method and solvent type significantly influence the total phenolic and flavonoid content and antioxidant activity. The total phenolic content varied from 1.37±0.59 to 5.23±0.87 mg GAE/mL extract, the total flavonoid content varied from 4.26±0.05 to 12.33±0.19 mg QE/g extract, and the antioxidant activity varied from 1.07±0.04 to 3.03±0.18 mg/mL. Based on these results, the ethanol extract of K. ceratophylla Haw. leaves demonstrate significant potential as a source for medicinal applications. The optimal extraction condition in this study was maceration with 95% ethanol, followed by freeze-drying, which produced the highest levels of antioxidant and flavonoid content. Future research should investigate the clinical implications and potential pharmaceutical formulations derived from K. ceratophylla Haw. Keywords: Antioxidants, K. ceratophylla Haw. leaf extracts, metabolite profiling, total flavonoids, total phenolics